Cultivating Humility in Business Education: A Listening-Focused Pedagogy for Future Leaders - Lehmann, Michal (Journal of business ethics, 2026)
In an era when humility and connection are vital for peace and sustainability, many leaders in business and government fall short by prioritizing their self-interest over ethics. Business schools, as key institutions shaping future leaders, may inadvertently reinforce this imbalance. To shift this lean toward self-interest, we propose a listening-focused pedagogy to cultivate humility and character in business school students. High-quality listening fosters interpersonal connection and promotes complex reasoning. Complex reasoning about oneself and others is a cornerstone of humility, which is central to morality and business ethics. We hypothesized that acquiring listening skills would enhance both high-quality listening and humility. To test this, we conducted a longitudinal quasi-experiment over four academic years (2018-2021) with data from 260 MBA students. Our findings show that the listening-focused course significantly increased students' listening skills and humility compared to control courses. These results demonstrate the course’s potential to have a meaningful influence on the character development of business students. We conclude by discussing theoretical and practical implications for business ethics education, offering our materials to support replication and the broader application of this pedagogy.